Matrix-Dependent Corridor Effectiveness and the Abundance of Forest Birds in Fragmented Landscapes - Vergara-Egert, P (2011)
Corridor function for wildlife movement constitutes an important and desirable ecological characteristic of linear landscape structures. Changes in the matrix conditions, however, may result in substantial changes in the mechanisms responsible for the use of corridors by animals. I developed a model that describes the influence of matrix quality on the effectiveness of corridors for wildlife movement and the abundance of animals in the corridors. The model predicts that corridor effectiveness is maximized at intermediate matrix quality levels, while the abundance in the corridor increases asymptotically with matrix quality. I tested predictions of this model by comparing the expected and observed relative abundance of forest bird species in two landscape types of southern Chile. In nine out of 12 cases the model correctly predicted the relative abundance of forest birds. Riparian forest strips were expected to be effective functioning as corridors for five out of six studied species, although corridor effectiveness for each species varied between landscape types. A reasonable strategy to improve connectivity is to maintain (or to increase, if necessary) the matrix quality at a level such that corridors can function efficiently as both drift fences and movement conduits. © 2011 Springer Science+Business Media B.V.